Facebook satisfaction and its impacts on fundraising: a case study at a Portuguese non-profit organization - Laureano, R. M. S. (2018)
Non-profit organizations have invested in the development of content for their Facebook pages, believing be an efficient and effective means to publicize its mission and raising resources, whether monetary or human. The purpose of this study is to assess the satisfaction of the participants with the Facebook page, and how that satisfaction influences the dissemination of the organization through the word-of-mouth and the donations practices. In this context, a questionnaire was administered to 204 participants that were aware of the Portuguese non-profit organization “Leigos para o Desenvolvimento” (People for Development). The results show that the participants are satisfied with Facebook page of the organization, and that there is influence of satisfaction on the word-of-mouth and on the frequency and amount of donations. However, satisfaction with the Facebook, itself, does not appear crucial to the realization of donations, either in the present or in future as intended. The study focuses only on one organization and includes a sample that may not represent all the population extracts and so inhibit the generalization of the findings to other populations. The paper includes implications for the development of an effective use of the Facebook as a digital marketing tool that can contribute to the sustainability of non-profit organizations. The study confirms the importance of the Facebook as a digital marketing tool that can contribute to the sustainability of non-profit organizations.